Photo-crosslinked adhesive hydrogel loaded with extracellular vesicles promoting hemostasis and liver regeneration - Xia, Wuzheng; Lai, Guanzhi; Li, Yichuan; Zeng, Cong; Sun, Chengjun; Zhang, Pinzhe; Zhu, Guanghao; Li, Leping; Wu, Linwei (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatectomy is an operation to remove local lesions in the liver, and it is also one of the most effective surgical methods for treating liver diseases. Although the liver itself has a regenerative function, fatty liver or cirrhosis will seriously affect postoperative liver function compensation and liver regeneration, and may also cause intraoperative massive bleeding. In this study, modified gelatin base (GelMA) and an additive (sodium alginate-dopamine, Alg-DA) were used to prepare a liver wound dressing hydrogel, which has good hemostatic function, excellent biocompatibility, and the ability to promotion of liver cell regeneration. The prepared GelMA/Alg-DA-based hydrogels had a porous structure with a porosity above 65%. Rheological studies showed that the prepared hydrogels could be stably in a gel state after being cured by ultraviolet light. Physicochemical characterizations suggested that the elastic modulus, water absorption, adhesion, and compressive properties of the prepared hydrogels were all improved with the increase of Alg-DA component content. In addition, all the prepared hydrogels could be degraded in vitro, and had good biocompatibility and hemostatic function. All test results showed that the GelMA/Alg-DA-1 hydrogel group had the best performance among all groups. Therefore, adipose-derived mesenchymal stem cells exosomes (AD-MSC-Exo) were successfully extracted and loaded into GelMA/Alg-DA-1 hydrogel. The composite hydrogel sustainably released up to 50% of exosomes over 14 days. Compared with the hydrogel without exosomes, GelMA/Alg-DA-1/Exo could effectively promote the cell proliferation and migration ability under the same conditions. In summary, the prepared composite hydrogel loaded with AD-MSC-Exo has great application potential in liver wound hemostasis and liver regeneration.